2016
DOI: 10.1016/j.soilbio.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the amino acid fingerprint in the unsterilized rhizosphere of a legume in relation to plant maturity

Abstract: The exudation of low-molecular-weight compounds, such as amino acids, contributes to the structure of rhizospheric microbial communities and plays a crucial role in nutrient mobility throughout the vegetative cycle of the plant. Due to their low concentration and their constant removal by microorganisms, the study of amino acids is difficult in unsterilized rhizospheric soil. Our aim was to investigate the dynamics of amino acids in unsterilized soil. Since there was currently no available method to estimate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Analyses were carried out according to Bobille et al . (), except for the elution profile: 70°C for 5 min, linear gradient of 5°C min −1 to 300°C, 300°C for 5 min, resulting in a total run time of 56 min. For the detection of sugars, samples were diluted 1:80 and analysed by HPLC at 30°C with 10% (m/v) NaOH on a Carbopac PA‐1 column (Dionex Corp., Sunnyvale, CA, USA) using pulsed amperometric detection, as described by Tetteroo et al .…”
Section: Methodsmentioning
confidence: 99%
“…Analyses were carried out according to Bobille et al . (), except for the elution profile: 70°C for 5 min, linear gradient of 5°C min −1 to 300°C, 300°C for 5 min, resulting in a total run time of 56 min. For the detection of sugars, samples were diluted 1:80 and analysed by HPLC at 30°C with 10% (m/v) NaOH on a Carbopac PA‐1 column (Dionex Corp., Sunnyvale, CA, USA) using pulsed amperometric detection, as described by Tetteroo et al .…”
Section: Methodsmentioning
confidence: 99%
“…How these amino acids might regulate FVG production and the significance of decreasing production of FVG in their presence is unknown. However, acidic amino acids and their amides may modulate FVG expression in the rhizosphere as they are exuded by roots [48,49]. Further, it has been shown that microbial products can enhance efflux of amino acids from roots [50].…”
Section: The Transcriptome Of Gvg Cluster Mutants Reveals Involvementmentioning
confidence: 99%
“…Our differential expression data indicate that ∆gvgR, A, and C strains have increased transcription of genes necessary for motility and chemotaxis and phenotypic analysis shows these mutants are more motile. In addition, in the presence of glutamate, an amino acid shown to be abundant in some root exudates [48,49], motility of WT WH6 increases while production of FVG decreases. This suggests a tradeoff between FVG production and increased capacity for rhizosphere colonization.…”
Section: Genes Involved In Rhizocompetence Are Upregulated In the Absmentioning
confidence: 99%
“…Amino acid concentrations in the sap exudates were determined by gas chromatography-mass spectrometry (GC-MS). Extraction of 10 μL or 50 μL and purification of amino acids on cation-exchange column (DOWEX 50W-X8) and their quantification with a 436-GC coupled to a simple quadruple SCION MS (Bruker), were carried out according to Bobille et al (2016).…”
Section: Measurements Of Amino Acids In Tissues and Sap Exudatesmentioning
confidence: 99%